Cross platform networking framework to simplify mobile application development - Cristina, Federico
The need for sharing information among mobile devices exists in many applications, and almost every data exchange between these devices involve the same requirements: a means for discovering other mobile devices in a wireless network, establishing logical connections, communicating application data, and gathering information related to the physical connection. This paper presents a cross platform open-source developer-oriented framework that acts as a support layer for host discovery, data communication among devices, and quality of service monitoring. Its purpose is to simplify the issues related to networking for mobile application developers. Currently, the framework is implemented for different platforms, such as Android, J2SE, and J2ME.